IMPLEMENTATION DIGITALIZATION OF PUBLIC SERVICE IN WEST JAVA PROVINCE: A STUDY OF THE SAPAWARGA PROGRAM - Albert Januar Christian (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
This research was motivated by the technological development of the Industrial Revolution 4.0, which then gave rise to digitalization products. The digitalization process has also penetrated the public sector, so that the public's need for the presence of technology-based public services is increasing. This study is intended to analyze how the implementation process of digitizing public services, especially in West Java Province through the Sapawarga Jabar Super App program, which is seen from several success factors. The research design used in this study uses a descriptive method using a qualitative approach. Then the data collection technique used in this study is in the form of a literature study. While the data analysis technique in this study uses the data triangulation method. Then the process of presenting the data, carried out by filtering data that researchers consider important regarding how the implementation of the Sapawarga Jabar Super App program. Then finally, the conclusion on how the implementation of the Sapawarga Jabar Super App program in the context of digitizing public services in West Java Province. While the analysis of the results and discussion in this study is focused on analyzing data reviewed from the factors of Digital Leadership, Culture, and ICT Infrastructure.